Assessment of changes occurring in biochar/zeolite substrates used in the vegetation-activated sludge process in the treatment of leachate from landfills - Aleksandra Wdowczyk; Agata Szymańska-Pulikowska; Jacek Chęcmanowski; Krzysztof Kierzek; Paweł Wiercik (Water Resources and Industry)
Leachate management remains one of the key technological challenges in landfill operations. There is a growing need for methods that can effectively treat leachate directly at its source. One promising approach is the vegetation-activated sludge process (V-ASP), which integrates constructed wetlands with conventional activated sludge treatment. Given the limited research on V-ASP systems, this study explored the potential of low-cost adsorbent materials—zeolite and sunflower husk biochar—to enhance leachate treatment. The absorption properties of these materials in various V-ASP configurations were analysed using Fourier Transform Infrared Spectroscopy (FTIR) and scanning electron microscope (SEM) to better understand the mechanisms involved in pollutant removal. For most of the parameters analysed (Chemical Oxygen Demand, total nitrogen, organic nitrogen, total phosphorus, nitrites, sulfates, chlorides, Zn, Cu, Ni), the best reductions were achieved with zeolite substrates at a hydraulic retention time (HRT) of 14 days. Ammonium nitrogen removal was highly efficient, maintaining rates between 99 % and 99.8 % throughout the entire experimental period. Total nitrogen removal varied, with a minimum reduction of 13.1 % and a maximum of over 74 %. FTIR spectra confirmed alterations in the functional groups and surface characteristics of zeolite and biochar, evidenced by shifts in the bands of functional groups due to absorption. These findings could help improve leachate management strategies and aid in designing treatment systems that can be deployed directly at landfill sites.